Queer Settlers: Questioning Settler Colonialism in LGBT Asylum Processes in Canada - Katherine Fobear (Refuge, 2014)
Refugee and forced migration studies have focused primarily on the refugees’ countries of origin and the causes for migration. Yet it is also important to also critically investi- gate the processes, discourses, and structures of settlement in the places they migrate to. This has particular signifi- cance in settler states like Canada in which research on refugee and forced migration largely ignores the presence of Indigenous peoples, the history of colonization that has made settlement possible, and ways the nation has shaped its borders through inflicting control and violence on Indigenous persons. What does it mean, then, to file a refugee claim in a state like Canada in which there is ongoing colonial violence against First Nations communities? In this article, we will explore what it means to make a refugee claim based on sexual orientation and gender identity in a settler-state like Canada. For sexual and gender minority refugees in Canada, interconnected structures of col- onial discourse and regulation come into force through the Canadian asylum and resettlement process. It is through this exploration that ideas surrounding migration, asylum, and settlement become unsettled.